Peculiarities of the Formation of the Innovative Economy in Some Asian Countries: Learning of Experience for the Russian Federation - N. V. Zakharova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
In the article the peculiarities of the formation of the innovative economy in some Asian countries are discovered. The main stages of the formation of the innovative economy in Singapore, Japan, South Korea are analyzed in details. On the basis of studing of vast statistical & theoretical material the main advantages of the innovation economy in the conditions of modern globalization are discovered. The connection between the innovative economy and the global competitiveness of the countries is proved, The main peculiarities of the formation of national innovation systems in Singapore, Japan, South Korea are shown. On the basis of the vast amount of the material the weak and the strong points of the innovative development of different countries and also the perspectives for their development are shown. What experience can be applied for Russian conditions is demonstrated.